Ruminant genetic resources of Karnataka state: Status, distribution and characteristics - BEHL, RAHUL; BEHL, JYOTSNA DHINGRA; KULKARNI, V S; JAIN, ANAND (The Indian Journal of Animal Sciences, 2023)
This article attempts to evaluate the present status and distribution of the ruminant genetic resources of Karnataka state vis-a-vis the exotic/crossbred and non-descript animals. The characteristics of the breeds of the ruminant species of the Karnataka state, including the new populations and breeds recently identified in the state like Dharwari and South Kanara buffaloes, Mouli and Yalga sheep and Nandidurga and Bidri goats, are also discussed. The total population of ruminant livestock, comprising cattle, buffalo, sheep and goat in Karnataka is 28.673 million. The density of 149.50 ruminants per km2 in this state is only marginally less than the national average of 160.15. However, the density of sheep at 57.62 per km2 is two and a half times than the national figure of 22.59. During 20012-2019, the total cattle and buffalo population have registered a decline of 11.01 and 14.00%, whereas, the sheep and goat population has shown an increase of 15.31 and 28.31%. During 2007-2012, periods for which the breed-wise data is available, the population of pure indigenous cattle, buffalo, sheep and goat have dwindled by 37.71, 32.93, 27.86 and 69.00%, compared to only -9.39, -19.79, 0.26 and -22.05% change in the total population of these species, respectively. Serious conservation efforts are required to arrest this decline in the ruminant genetic resources of the state of Karnataka.